Metode Penanaman Nilai-nilai Religius dalam Keluarga untuk Meningkatkan Kesadaran Beragama Remaja di Kecamatan Batahan Kabupaten Mandailing Natal - Mariatul Ummah; Zulhammi Zulhammi; Hamdan Hasibuan (ISLAMIKA, 2023)
This study aims to determine the efforts to instill religious values in the family in order to increase adolescent religious awareness in the Batahan sub-district, Mandailing Natal Regency. As well as to find out the supporting and inhibiting factors in the cultivation of religious values in the family in order to increase adolescent religious awareness in Batahan sub-district, Mandailing Natal district. This research uses a qualitative approach with descriptive methods. The results showed that: 1. Efforts to inculcate religious values in the family to increase adolescent religious awareness in Batahan District, Mandailing Natal Regency were carried out using several methods, namely the exemplary method, the habituation method, the supervision method, the advice method and the punishment method. This is done so that children always have good behavior and have a high level of religious awareness so that children do not fall into unwanted things. 2. Factors supporting the inculcation of religious values in the family to increase adolescent religious awareness in Batahan District, Mandailing Natal Regency, namely having a harmonious family, being in a healthy social circle, and having a good living environment. while the inhibiting factors for instilling religious values in the family to increase adolescent religious awareness in Batahan District, Mandailing Natal Regency are children who are in a less harmonious family condition, low socioeconomic status, children have unhealthy associations and are in a lively environment. full of bad influences.